Self-inflicted chemical burns caused by depilatory cream use: The price of beauty - Rachel H Park; Trevor C Hansen; Derek E Bell (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective was to study and describe the presenting patient characteristics for those with chemical burns acquired from hair removal beauty products. Methods: Retrospective single-center chart review was done to identify all burn injuries caused by the use of depilatory cream use. Results: A total of seven patients who acquired burn injuries due to depilatory cream use were identified. Six were female and one was male. Patients' age ranged from 3 to 43 years, with a mean age of 27.2 years. Total body surface area of the burns ranged from 0.18% to 0.79% including first- and second-degree burns; none of the patients acquired third-degree burns. Most of the injuries involved groin and pubic area. All patients were treated with wound care, and none required inpatient care. All of the patients who presented to follow-up visits showed re-epithelialization and good healing. Conclusion: Depilatory cream is a corrosive chemical hair removal agent that can lead to unintended chemical burns if used improperly. Burn-care provider, as well as other health-care providers, should be aware of this unusual cause of chemical burn and educate their patients appropriately.